(untitled) (Jurnal Bahasa, 2019)
Various policies enacted in education sector to ensure teenagers in future have good speech skill. This study case was conducted to identify politeness strategy and explaining an aspect that emphasizes teen speech skill when interacting. This study case is accompanied by teenagers who are 16 and 17 years old, who live and study at Maktab Rendah Sains MARA (MRSM), Baling Kedah. The teenagers involved are also teenagers who follow two certificate programme at MRSM, Baling, Kedah. This study case involves two types of interaction, that is to say spontaneous interactions and planned interactions. Interactions session was recorded using an audio recorder and then transcribed to analyse using Politeness Strategy Theory Brown and Levinson (1987). The result of the analysis will be used to emphasize teen speech skill when interacting spontaneously and planned. The finding show that teenager’s speech skill when interacting is identified through several aspects of language use. In this case, linguistic aspects related to language usage rules that emphasize the accuracy of language form and language build. Therefore, teenagers need to equip themselves with knowledge through reading in order to reinforce teen speech skill to better interact. Keywords: speech skill, politeness strategy, teenagers, spontaneous interactions, planned interactions